Dementia beyond 2025: Knowledge and uncertainties. (January 2016) - Kenigsberg, Paul-Ariel; Aquino, Jean-Pierre; Bérard, Alain; Gzil, Fabrice; Andrieu, Sandrine; Banerjee, Sube; Brémond, François; Buée, Luc; Cohen-Mansfield, Jiska; Mangialasche, Francesca; Platel, Hervé; Salmon, Eric; et al.
Given that there may well be no significant advances in drug development before 2025, prevention of dementia–Alzheimer's disease through the management of vascular and lifestyle-related risk factors may be a more realistic goal than treatment. Level of education and cognitive reserve assessment in neuropsychological testing deserve attention, as well as cultural, social, and economic aspects of caregiving. Assistive technologies for dementia care remain complex. Serious games are emerging as virtual educational and pleasurable tools, designed for individual and cooperative skill building. Public policies are likely to pursue improving awareness and understanding of dementia; providing good quality early diagnosis and intervention for all; improving quality of care from diagnosis to the end of life, using clinical and economic end points; delivering dementia strategies quicker, with an impact on more people. Dementia should remain presented as a stand-alone concept, distinct from frailty or loss of autonomy. The basic science of sensory impairment and social engagement in people with dementia needs to be developed. E-learning and serious games programs may enhance public and professional education. Faced with funding shortage, new professional dynamics and economic models may emerge through coordinated, flexible research networks. Psychosocial research could be viewed as an investment in quality of care, rather than an academic achievement in a few centers of excellence. This would help provide a competitive advantage to the best operators. Stemming from care needs, a logical, systems approach to dementia care environment through organizational, architectural, and psychosocial interventions may be developed, to help reduce symptoms in people with dementia and enhance quality of life. Dementia-friendly environments, culture, and domesticity are key factors for such interventions.